Integrating Gender Into Poverty Reduction Strategies: From the Declaration of Intent to Development Policy in Practice? - Birte Rodenberg (Deutsches Institut für Entwicklungspolitik (DIE), 2002)
Worldwide, 1.3 billion people are living in extreme poverty. Most of them are women. The international community has thus come to realize in recent years that political, economic, and cultural discrimination against women constitutes a central obstacle to social development. New policy guidelines of bi- and multilateral donors affirm that poverty reduction programs can succeed only if they take into consideration the existing social inequality between men and women. At present the concern is therefore a twofold one: to ensure that women have access to resources and rights and to initiate measures aimed at overcoming structural discrimination. The paper examines the extent to which the National Poverty Reduction Strategy Papers (PRSPs) called for in connection with the enhanced debt initiative are in line with this demand and contain an integrated gender perspective. Involvement of poor, politically underrepresented groups in the PRSP process is intended to ensure that the current poverty-reduction programs take account of their interests. Women's organizations are also participating in these processes. There is, however, for the most part no systematic inclusion of women's positions. One factor that constitutes an essential obstacle to the development of long-term strategies to reduce women's poverty is a lack of data broken down and analyzed in gender-specific terms. Poverty profiles and indicators are generally limited to the access rate of girls and women to basic education. Thus far no success has been met with in integrating a gender-specific perspective into the poverty strategy's macroeconomic framework. The PRSP process takes no consideration of the social impacts on women of conventional stabilization and privatization measures. Measures aimed at improving the economic situation of women are largely limited to the provision of microcredit. In the PRSP implementation process in particular, the bilateral donors sought to devote more effort to integrating cross-sectoral issues like promotion of gender equity. The policy dialogue with governmental and nongovernmental actors ought to be used to link the gender issue with macroeconomics, promotion of democracy (participation), and the coherence of sectoral policies.
Keywords: 330